Síntese e caracterização de óxidos metálicos nanocristalinos - Gomes, Maria de Andrade (2014)
The aim of the present work were the synthesis of metal oxide nanoparticles via different synthesis routes and the investigation of the influence of synthesis procedures on structural, morphological and luminescent properties of the samples. The materials under investigation in this work were zinc oxide (ZnO) and yttrium oxide (Y2O3), pure and doped with rare-earth elements. These systems have large applicability in photonic devices, catalyst, luminescent labels for diagnostic and therapy. Three synthesis routes were used for the production of the powders, namely, proteic sol-gel, PVA (polyvinyl alcohol)-assisted sol-gel and hydrothermal. The routes satisfactorily allowed the production of the studied materials with nanoparticles in the size range appropriate for the potentially applications. For ZnO samples, it was observed great influence of the synthesis procedure under morphological and luminescent properties of the nanoparticles. Samples calcined at low temperature present intense UV emission. On the other hand, the powder thermally treated at higher temperatures produced efficient visible luminescence over a wide range of energies. Additionally, ZnO samples prepared via sol-gel techniques showed catalytic activity. The synthesis methods allowed the formation of Y2O3 nanoparticles with different sizes, which in turn present strong influence on the fluorescent emission of Nd doped samples. In Eu3+/Tb3+ codoped Y2O3 samples, the relative intensity of the emission peaks could be changed by varying the excitation wavelength, due to energy transfer processes between doped ions. Magnetic-fluorescent nanocomposite produced via coupling reactions between Y2O3:Eu and Fe2O3 nanoparticles, present luminescent and magnetic characters, confirming their applicability as bi-modal tool for therapy and diagnosis of cancer cells.